1972
DOI: 10.1002/eji.1830020507
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated target cell lysis by non‐immune cells. Characterization of the antibody and effector cell populations

Abstract: Max-Plan&-I nstitut fur I mmunbiologie, Frei bu rg/Bng. Antibody-mediated target cell lysis by non-immune cells. Characterization of the antibody and effector cell populationsCells from normal rabbit thymus, lymph node and spleen demonstrated in vitro cytolytic activity when incubated with antibody-coated target cells. High dilutions of antibody were effective, and the degree of lysis was dependent on the lymphocyte-target cell ratio, In the spleen, two populations of effector cells were defined -one populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…One apparent difference between ABCIL and LDA is that autologous cells do not generally act as effector cells against autologous targets in the presence of ABCIL antibody, but they do in the presence of LDA. We believe that the ABCIL system is c'losely linked to those recently described (Gelfand et al 1972, Holm & Perlmann 1969, Mijller & Svehag 1972, Wunderlich et al 1971 and that our results fit the hypothesis of Moller as modified by Fakhri & Hobbs (1972). Lymphocytes ( T or B or both) carry a receptor for the Fc of immunoglobulin molecules that have become activated, for instance, by Fab attachment of the antibody to its target.…”
Section: I X U S J I O Nsupporting
confidence: 85%
See 1 more Smart Citation
“…One apparent difference between ABCIL and LDA is that autologous cells do not generally act as effector cells against autologous targets in the presence of ABCIL antibody, but they do in the presence of LDA. We believe that the ABCIL system is c'losely linked to those recently described (Gelfand et al 1972, Holm & Perlmann 1969, Mijller & Svehag 1972, Wunderlich et al 1971 and that our results fit the hypothesis of Moller as modified by Fakhri & Hobbs (1972). Lymphocytes ( T or B or both) carry a receptor for the Fc of immunoglobulin molecules that have become activated, for instance, by Fab attachment of the antibody to its target.…”
Section: I X U S J I O Nsupporting
confidence: 85%
“…Antibody-sensitized target cells will induce lymphocyte-mediated cytotoxicity in lymphocytes from normal noninimunized mouse (Dennert & Lennox 1972, van Boxel et al 1972, rabbit (Gelfand et al 1972), and human donors (Carrlson et al 1971, Holm & Perlman 1967, Moller & Svehag 1972. In these systems the antibody-sensitized target cells have been tumor cells, cultured fibroblasts, or even xenogeneic erythrocytes.…”
mentioning
confidence: 99%
“…The latter possibility seems unlikely on numerical grounds since, as shown previously, only very few T cells (up to 3%) express both the Fc and T cell marker [17]. Similar uncertainties about the true nature of lymphoid K cell(s) in other species have been recorded with some sug gesting that the lymphoid K cell is a non-T lymphocyte [7, 12-14, 23, 30, 39], whereas others identify K cells as T lymphocytes [5,11,20,38], To decisively show that the bovine lymphoid K cell is a T cell will require methods designed to selectively remove all T cells but no other population. Such methods are not as yet available since erythrocyte rosetting does not detect all T cells and the rosettes are too unstable to permit clean separation on Ficoll-Hypaque gradients in the bovine species.…”
Section: Discussionmentioning
confidence: 82%
“…A clear definition of the nature of lymphocyte sub sets responsible for ADCC in different spe cies has been the goal of many investigators (4, 7, 12-14, 21, 28, 31, 39, 40], Some of the earlier studies had claimed that lym phoid K cells possess B cell characteristics [9,42,44] but the bulk of evidence favors the hypothesis that a null lymphocyte (e.g., neither B nor T) is the predominant K cell in most species. However, some recent stud ies have suggested that T cells may act as K cells against some targets [5,11,20,28,37,38], and the human B cell was clearly shown to act as a K cell against lymphoblastoid cell targets by Eremin et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…I n the other mechanism, contact between the tumor cell and the lymphocyte is mediated by tumor-specific antibody. The lymphocytes which participate in this reaction are characterized by the presence of membrane receptors for the Fc region of antigen-complexed immunoglobulin (Gelfand et al, 1972;Moller and Svehag, 1972). There is considerable controversy concerning the various types of cells which can participate in the antibody-dependent reaction, but lymphocytes with this potential apparently are not dependent upon thymic influence (Harding et al, 1971 ;Van Boxel at al., 1972), and they need not be sensitized to the tumor antigen in order to effect the cytolytic react ion.…”
mentioning
confidence: 99%